Trading preferentially - GBEDOAH, Richard (KDI School, 2017)
This paper investigates Ghana-EU trade under the new Economic Partnership Agreement (EPA). The study seeks to examine the influence of the EPA on trade from the Ghanaian perspective. Using qualitative methods, focusing on review of trade literature from Eurostat, European Trade Commission, and Ghana’s Ministry of Trade and Industry and other relevant sources, analysis is made to highlight impacts of the trade agreement on Ghana’s trade sectors. Trade Data from 2005 to 2015 has been utilized in making analyses. The study finds that although the agreement has improved measures aimed at trade facilitation and in extension services trade, it is posing negative effects to trade in goods. Inability of Ghanaian producers to compete with European imports threatens the industry. Also, the exclusion list of Ghana is inadequate in protecting agricultural trade, especially in the absence of tariff measures. Finally, a regional EPA is likely to worsen Ghana’s competitive position in the regional market. Taking these findings together with the decreasing attractiveness of the EU market for Ghanaian exporters, the paper recommends a review of the terms of the EPA. The study also recommends enhanced commitments and efforts from the EU (aid) to help transcend the tariff losses and other adjustment costs associated with the EPA.
Thesis(Master) --KDI School:Master of Public Policy,2017